A quantitative assessment of hydrological responses to climate change and human activities at spatiotemporal within a typical catchment on the Loess Plateau, China. (30th August 2019) - Lyu, Jiqiang; Mo, Shuhong; Luo, Pingping; Zhou, Meimei; Shen, Bing; Nover, Daniel
Abstract: It is important to understand the relative contributions of climate change and human activities to changes in runoff to sustainably manage water resources in the arid Loess Plateau, China. In this study, Chabagou River Basin in the central arid region of the Loess Plateau was selected to investigate changes in runoff, within which a series of soil conservation measures have been implemented since the late 1950s. We applied the non-parametric Kendall test (MK) and the Bayesian change point (BCP) method to identify trends and potential change points in hydro-meteorological data sequences. The results of the MK test revealed no significantly abrupt variation has been detected in annual hydro-meteorological data sequences, while a number of potential change points were identified using the BCP method applying different posterior probabilities. We also systematically review two commonly applied quantitative methods that draw on both empirical statistics and hydrological modeling to quantify the impact of climate change, human activities and meteorological variation on mean annual runoff at spatiotemporal scales based on precipitation, evapotranspiration, runoff-precipitation coefficients, and soil water throughout the river basin. The results of this study show that climate change and normal climate variability are responsible for about 80% of the decrease in runoff, mainly due to reduced precipitation, while human activities was responsible for <20% of reductions in runoff. The results also show that soil conservation measures have influenced hydrological processes at spatiotemporal and that runoff within the Chabagou River Basin (CRB) is more sensitive to spatial distribution of soil conservation measures than meteorological factors. The relative contributions to runoff variations that derive from climate change, human activities and meteorological variation were calculated in this study, but interactions between climate change and human activities is complex, and not easy to be separated.